THE PROBLEM OF PHILOSOPHICAL-ANTHROPOLOGY IN THE RELIGIOUS-PHILOSOPHICAL TEACHING OF IBN AL-ARABI (American Journal of Research in Humanities and Social Sciences, 2024)
This scientific article briefly addresses Ibn al-Arabi's mysticism, the general direction of his mysticism, the natural structure of humans, the history of natural structure, His divine-religious views in the fields of philosophy and mysticism, his scientific works and their meaning and essence.